Changes in appetite during quarantine and their association with pre-COVID-19 mental and physical health. (1st September 2022) - Rodriguez-Moreno, Diana V.; Vazquez, Sima; Cheslack-Postava, Keely; Xu, Guangling; Cycowicz, Yael M.
Abstract: Background: The COVID-19 Pandemic resulted in high levels of fear, anxiety, and stress. People with pre-existing physical and mental health conditions may have been more affected by the sudden changes in daily habits during the initial months of global quarantine imposed during the COVID-19 pandemic. Methods: We designed the Quarantine, Anxiety, and Diet (QUAD) Survey to investigate the effect of pre-existing health conditions on the relationship of COVID-19 stress and food behavior. The anonymous survey was distributed online and only adults were eligible to participate. Results: The results showed that responders with pre-existing health conditions differed from healthy participants in eating behavior during this time of stress. Compared to those classified as healthy, fewer people with pre-existing physical illness showed an increase in appetite with stress during the COVID-19 pandemic. Responders with pre-existing psychiatric illness were more likely to show increases or decreases in appetite with stress compared to healthy responders. Furthermore, higher BMI was associated with higher rate of increased appetite, whereas low BMI showed a higher rate of decreased appetite, both compared to normal BMI. Conclusion: The QUAD Survey demonstrated that individuals with pre-COVID-19 psychiatric conditions are at a higher risk of maladaptive food behavior under stress. Since pre-existing psychiatric illnesses and acute stressors are known risk factors for eating disorders, special attention should be placed on those at risk to mediate the psychological and physical effects of stress and anxiety.